Impact of fine arts education on psychological wellbeing of higher education students through moderating role of creativity and self-efficacy - Jin, Xuguang; Ye, Yuan (Frontiers in Psychology, 2022)
The purpose of our research was to explore the impact of fine art education on psychological wellbeing among undergraduate students through moderating role of creativity and self-efficacy. Art is the most effective medium for expressing human ideals, culture, identity, life styles, emotions, and societal experiences. Cross-sectional research was carried out on 376 undergraduates in the 2022–2023 academic year at the Public and Private Chinese universities, and those students who currently enrolled in Fine arts courses. A link to the Google Doc survey was sent through email and social media channels (i.e., WeChat). The timeframe of the data collection was three months, from February 2022 to April 2022. While analyzing the obtained data, we used IBM SPSS version 25, which includes both descriptive and inferential statistics. The overall results of the study indicate that the fine art education positively and significantly influence psychological wellbeing. Moreover, findings also indicates that the creativity and self-efficacy positively and significantly moderates the relationship between fine art education and psychological wellbeing. The study highlighted the significance of fine art education in Chinese students. Through, this study students studying in this field should be made more aware of the importance of fine art education and its link with psychological wellbeing. Further, art courses should be added to the curriculum at different levels of education to boost the creativity and self-efficacy in higher education students in China. Implications for parents, students, and teachers are also discussed.